Compressive strength and Weibull distribution of lithium disilicate dental ceramics: Kekuatan tekan dan distribusi Weibull dari keramik dental disilikat lithium - Silvia Naliani; Dahlia Sutanto; Angela Evelyna; Michael Adi Hizkia (Makassar Dental Journal, 2021)
Objective: To compare the compressive strength of three types of commercial lithium disilicate ceramics. Methods: Three groups of lithium disilicate ceramics (IPS e.max Press, Vintage LD Press, and Celtra Press) total of twelve cylindrical specimens (diameter 4 mm x length 6 mm) were produced by laboratory processing. The compressive strength was conducted using Shimad-zu universal testing machine with load cell F 50 kN, cross head speed of 1 mm/s. Micromorphology were observed using scan-ning electron microscope. Anova test and Weibull test were performed and p<0.05 was considered significant. Results: There are no significant differences between three groups of lithium disilicate dental ceramics compressive strength (p=0.531). How-ever, IPS e.max Press group show higher compressive strength compared to the other two materials. IPS e.max Press and Vin-tage LD Press groups show significantly higher coefficient corelation than Celtra Press group. Conclusion: IPS e.max Press lithium disilicate dental ceramic have higher compressive strength compared to the other groups, but the reliability of Celtra Press is lower than those of lithium disilicate dental ceramics.